Scanning force microscopy study of the ferroelectric phase transition in triglycine sulfate - Orlik, X.K.; V. Likodimos; Pardi, L.; Labardi, M.; Allegrini, M. (Applied Physics Letters, 2000)
Voltage-modulated scanning force microscopy is applied to study the temperature dependence of the ferroelectric domain structure of triglycine sulfate up to TC, the ferroelectric transition temperature. The polarization image contrast exhibits a power-law decrease as TC is approached, associated with the competition between Maxwell stress and the converse piezoelectric effect. Substantial differences in the static and dynamic domain patterns are detected for two samples of different aging conditions. © 2000 American Institute of Physics.
cited By 17